Analisa Penerapan Sistem Manajemen Mutu Berbasis ISO 9001:2005 pada Perusahaan PT. Waskita Karya - Heni Fitriani (Universitas Teuku Umar, 2022)
ISO 9000 is a process standard established to demonstrate that a company has a comprehensive and specialized quality system. ISO 9001:2015 is a worldwide accepted QMS benchmark. The International Organization for Standardization (ISO) points out that the ISO 9001:2015 quality management system is based on seven principles, namely, customer focus, leadership, people involvement, process approach, improvement, decision making and relationship management. This study aims to determine how the implementation of ISO 9001:2015 and the level of implementation of ISO 9001:2015 at PT. Waskita Karya on the Kayu Agung – Palembang – Betung Toll Road Project. The research was conducted by distributing questionnaires directly. The data collected in this study were 10 respondents. From the results of this study, it was found that the level of implementation of ISO 9001:205 in the quality management system of the Kayu Agung - Palembang - Betung Toll Road Construction project by PT. Waskita Karya has obtained very good results because from clause 4 to clause 10 the value obtained is 90.4%. In addition, PT. Waskita Karya made a quality policy called Waskita Procedure (PW) based on ISO 9001:2015, where the policy must be applied in all parts of PT. Waskita Karya.